Students' Perception of Using Google Meet In English For Advertising Class at Universitas Bhinneka PGRI - Gita Yulia Setiawan (Program Studi Pendidikan Bahasa Inggris Kabupaten Kepulauan Aru, 2022)
Indonesian’s students always does teaching learning process at school, but, the students can not do it during pandemic covid 19. To overcome this situation, there are some exchanges that is made. One of some exchanges is from face to face teaching learning process to online.Some applications as part of technology development are used to support teaching learning process. Eight semester students of English Department Universitas Bhinneka PGRI also face that. They use google meet to support English for Advertising class. The purpose of this study was to find out the lecture‟s way in conducting English for Advertising class and to know eighth semester students' perceptions by using google meet in English for advertising class during pandemic covid 19 at the English Department of Bhinneka PGRI University. In this study, the researcher used a qualitative descriptive method and data is random sampling data. Participants are eighth semester students who joined in English for advertising class at Universitas Bhinneka PGRI. It involves 25 students.Data collection methods used in this study were questionnaire and interview. As the results, it is found that From 21 statements, the students give 16 positive perception, 5 neutral, and nothing negative perception of the statements. From results of quetionnaire, most of the students give positive perception. And from the result of interview showed that the lecture always conduct teaching learning process by discussion method which is followed by assigmnents without giving motivation and feedback every meeting. Most of the students are happy and enthusiasm at the class.